2001
DOI: 10.1115/1.1370501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Magnetic Modulation on the Stability of a Magnetic Liquid Layer Heated From Above

Abstract: The effect of a time-sinusoidal magnetic field on the onset of convection in a horizontal magnetic fluid layer heated from above and bounded by isothermal non magnetic boundaries is investigated. The analysis is restricted to static and linear laws of magnetization. A first order Galerkin method is performed to reduce the governing linear system to the Mathieu equation with damping term. Therefore, the Floquet theory is used to determine the convective threshold for the free-free and rigid-rigid cases. With an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…An interesting case consists of applying an external magnetic field of a constant or spatially varying gradient. The effect of a time-sinusoidal magnetic field on the onset of convection in a horizontal magnetic fluid layer heated from above and bounded by isothermal non-magnetic boundaries has been considered by Aniss et al (2001). Self-oscillatory convection caused by the Soret effect in ferrofluids has been predicted by Shliomis and Souhar (2000).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting case consists of applying an external magnetic field of a constant or spatially varying gradient. The effect of a time-sinusoidal magnetic field on the onset of convection in a horizontal magnetic fluid layer heated from above and bounded by isothermal non-magnetic boundaries has been considered by Aniss et al (2001). Self-oscillatory convection caused by the Soret effect in ferrofluids has been predicted by Shliomis and Souhar (2000).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was analyzed for a liquid layer heated from below or from above (stable or unstable equilibrium configurations). Here the onset of convection presents a competition between harmonic and subharmonic modes; see for instance [3,8,9,[12][13][14][15][16]. A similar modulation to the gravitational one can be realized in a horizontal ferromagnetic liquid layer heated from above and submitted to a time-periodic external magnetic field instead of vertical vibrations [11,12].…”
Section: Introductionmentioning
confidence: 93%
“…Here the onset of convection presents a competition between harmonic and subharmonic modes; see for instance [3,8,9,[12][13][14][15][16]. A similar modulation to the gravitational one can be realized in a horizontal ferromagnetic liquid layer heated from above and submitted to a time-periodic external magnetic field instead of vertical vibrations [11,12]. The other type of modulation [14][15][16][17][18][19][20][21][22][23][24][25], in which the temperatures is oscillating at the boundaries, is mainly concentrated in a boundary layer whose thickness decreases with increasing frequency of modulation.…”
Section: Introductionmentioning
confidence: 96%
“…A previous theoretical investigation [1] has shown that the onset of convection in a horizontal magnetic fluid layer can be influenced by a time-modulated driving force. This driving force is induced by an external magnetic field, which can easily be time-modulated with the frequencies required for the investigations.…”
Section: Introductionmentioning
confidence: 99%